Auditoría tributaria, para el cumplimiento de la normativa fiscal en la compañía de transporte de carga pesada transgavilanez, periodo 2017” - Mariela Lisbeth, Chávez Palate (2020)
The research consists of a tax audit to verify fulfillment with the fiscal regulations of the Transgavilanez heavy freight Transport Company in the 2017 period of the city of Riobamba. The main objective for performing the tax audit to the entity referred above is verifying fulfillment with the tax rules identifying deviations of the company that affects achievement with tax obligations. The research has considered pertinent using five chapters that are detailed below: Chapter I: the frame of reference, chapter II: state of the art, chapter III: the methodological framework, chapter IV the results and analysis after executing the audit in the company, and finally in chapter V the conclusions and research recommendations.